2002
DOI: 10.1093/fampra/19.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of qualitative research: are there special issues for health services research?

Abstract: While recognizing the reservations held about strict ethical guidelines for qualitative research, we argue for further debate of these issues so that the health services research community can move towards the adoption of agreed standards of good practice. In addition, we suggest that empirical research is desirable in order to quantify the actual risks to participants in qualitative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
233
0
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(245 citation statements)
references
References 23 publications
0
233
0
12
Order By: Relevance
“…64 Practitioner-research, therefore, requires careful planning in order to minimise the risk to participants and to navigate issues of consent, confidentiality, misinterpretation and misrepresentation of data. These issues were addressed in accordance with ethical guidelines 65 at each stage of this research by the authors.…”
Section: Data Analysis and Representationmentioning
confidence: 99%
“…64 Practitioner-research, therefore, requires careful planning in order to minimise the risk to participants and to navigate issues of consent, confidentiality, misinterpretation and misrepresentation of data. These issues were addressed in accordance with ethical guidelines 65 at each stage of this research by the authors.…”
Section: Data Analysis and Representationmentioning
confidence: 99%
“…In a number of instances, qualitative research has been found to conflict with guidelines laid down by medical research ethics committees (Ramcharan & Cutcliffe 2001;Richards & Schwartz 2001). Research designs favoured by such committees often do not allow for the evolving nature of social-research questions and the range of people who may be involved in projects.…”
Section: Case Notes From Anthropologists In the Fieldmentioning
confidence: 99%
“…The researcher questioned if this recall of painful memories would do harm or provide comfort as it allowed an opportunity to be heard when conducting the interviews. Richards and Schwartz (2002) identified anxiety and distress as a potential risk area for participants. Questions are intended to be deep reaching to bring forth information.…”
Section: Yellow School Busesmentioning
confidence: 99%
“…Most participants knew of the university or knew someone who attended the university and could relate to the researcher. Richards and Schwartz (2002) described possible ethical risks to those participating in qualitative research. The risks included: "anxiety and distress; exploitation; misrepresentation; and identification of the participant in published papers by themselves or others" (p. 135).…”
Section: Given Enoughmentioning
confidence: 99%
See 1 more Smart Citation